Towards Acquiring the Environmental Skills and Trends Required to Achieve Environmental Architecture - Haider Majid Hasan, Dr.; ., . (International Journal of Engineering and Technology, 2018)
In the last decade of the last century, most countries in the world paid particular attention to the issues of environmental protection and sustainable development. This concern was not born in a vacuum. Environmental voices calling for reducing the environmental effects of various human activities called for reducing waste and contaminants and maintaining the natural resource base for the next generations.Â As a result, urban sectors are no longer isolated from the pressing environmental issues that have begun to threaten the world. In the last few years, these sectors have been considered to be one of the main consumers of the natural resources of land, materials, water and energy. On the other hand, the construction industry the complex and the result of large amounts of noise and pollution and solid waste. The problem of waste of energy and water remains one of the most important environmental-economic problems of the buildings because of the continuity and sustainability of the buildings throughout the period of operation of the building.For these and other reasons, and as a result of growing public awareness of the environmental impacts associated with construction activities, some specialists noted that the main challenge facing the urban sectors at this time is their ability to meet their commitments and fulfill their developmental role towards achieving comprehensive sustainable development concepts. On urban projects will be one of the most important competitive standards in these sectors in the 21st century. Hence, in the advanced industrial countries, new concepts and methods that were previously unknown in the design and implementation of projects have emerged. These include "sustainable design", "environmental architecture", "green architecture" and "sustainable buildings"These concepts are all new ways of design and construction that evoke the environmental and economic challenges that have cast a shadow over the various sectors of the age. The new buildings are designed, implemented and operated with advanced techniques and technologies that contribute to reducing environmental impactHence, the problem of research is the weakness of the methods that would achieve environmental architecture, while the methodology of research focused on descriptive analytical method in determining the methods and procedures necessary and the importance of acquiring skills to achieve environmental architecture and then the research reached a number of conclusions and recommendations.Â Â